Description of Coeliccia natgeo sp. nov. from Central Vietnam with keys to the males and females of the hayashii-group (Odonata: Zygoptera: Platycnemididae) - Phan, Quoc Toan; Ngo, Quoc Phu; Toan, Thai Canh; Tuan, Vo Anh (Zootaxa, 2020)
Coeliccia natgeo sp. nov. is described from central Vietnam (holotype ♂, 18.2708 N, 105.3431 E, Khe Nhop, Vu Quang National Park, Ha Tinh Province, deposited in the Zoological Collection of Duy Tan University, Da Nang City, Vietnam). The new species differs from other members of the hayashii-group by males lacking antehumeral stripes, spots and pruinosity on the synthorax and female having the central part of the posterior pronotal lobe reduced to a small projection. Keys to the males and females of the hayashii-group are provided.